Lactobacillus plantarum as Biopreservative Agent in Paneer for Dietary Food of Diabetic and Coronary Heart Disease Patients - Singgih, Marlia; Ahsogan, Kanaka L.; Puspitasari, Irma M.; Damayanti, Sophi (Indonesian Journal of Clinical Pharmacy, 2017)
Paneer is a food product that is obtained by heating milk followed by acid coagulation. It is known asa diet food that is recommended for diabetic and coronary heart disease patients. A relatively shortershelf life of paneer is considered to be a major hurdle in its production. The present preliminary studywas conducted to determine antibacterial activity of Lactobacillus plantarum against Eschericia coliand Bacillus cereus, to develop it as biopreservative agent in paneer before using it for dietary food ofdiabetic and coronary heart disease patients in next clinical study. The antibacterial activities were testedthrough Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC)using microdilution well method. Biopreservative activity in paneer was tested using total plate countmethod based on time and temperature variations. Result showed that Lactobacillus plantarum inhibitedBacillus cereus and Eschericia coli with MIC of 3125 and 1562.5 Î¼g/mL whereas MBC was in a value of>6250 and >3125 Î¼g/mL, respectively. As a biopreservative agent, addition of Lactobacillus plantarumto paneer showed no bacterial growth until 7 days in room temperature and 9th day in cold temperature. Itis concluded that Lactobacillus plantarum could be used as a natural biopreservative agent for extendingthe shelf life of paneer. The paneer with addition of Lactobacillus plantarum as biopreservative will thenbe consumed by diabetic patient and coronary heart patients in next clinical study.